Advances in Mn-Based Electrode Materials for Aqueous Sodium-Ion Batteries - Ding, Changsheng; Chen, Zhang; Cao, Chuanxiang; Liu, Yu; Gao, Yanfeng (Nano-Micro Letters, 2023)
Aqueous sodium-ion batteries have attracted extensive attention for large-scale energy storage applications, due to abundant sodium resources, low cost, intrinsic safety of aqueous electrolytes and eco-friendliness. The electrochemical performance of aqueous sodium-ion batteries is affected by the properties of electrode materials and electrolytes. Among various electrode materials, Mn-based electrode materials have attracted tremendous attention because of the abundance of Mn, low cost, nontoxicity, eco-friendliness and interesting electrochemical performance. Aqueous electrolytes having narrow electrochemical window also affect the electrochemical performance of Mn-based electrode materials. In this review, we introduce systematically Mn-based electrode materials for aqueous sodium-ion batteries from cathode and anode materials and offer a comprehensive overview about their recent development. These Mn-based materials include oxides, Prussian blue analogues and polyanion compounds. We summarize and discuss the composition, crystal structure, morphology and electrochemical properties of Mn-based electrode materials. The improvement methods based on electrolyte optimization, element doping or substitution, optimization of morphology and carbon modification are highlighted. The perspectives of Mn-based electrode materials for future studies are also provided. We believe this review is important and helpful to explore and apply Mn-based electrode materials in aqueous sodium-ion batteries. Highlights: 1 Mn-based electrode materials, including oxides, Prussian blue analogues and polyanion compounds, are introduced systematically for aqueous sodium-ion batteries. 2 The composition, crystal structure, morphology and electrochemical performance of Mn-based electrode materials are reviewed. 3 The improvement methods of electrochemical performance, such as electrolyte optimization, element doping or substitution, morphology optimization and carbon modification, are discussed.